El significado del: Shug Uma, Shug Shungu y Shug Shimi en la cosmovisión de los indígenas de la parroquia Licto, período 1970-2000 - Daniel, Mora (2020)
The name of this research is “The meaning of: Shug Uma, Shug Shungu and Shug Shimi in the indigenous worldview in Licto parish, from 1970 to 2000” This research was conducted in order to publicize the significance that indigenous consider to their customs and traditions, all through the cultural value that exists in the indigenous world. The meaning is not lost, but it is preserved and transmitted through new generations. Scientific, deductive and inductive methods were used for the methodology; the research is documentary, field research, descriptive and analytic; meanwhile the research design is a participatory action research type. By working in groups, it could be appreciated what the effect and the significance are about the mentioned trilogy the inhabitants from Licto parish. Be on solid, there is a well-articulated commitment in order to work together, developed and make decisions by collective participation. The commitment get started with the cooperation and collaboration of all stakeholders. Finally, the indigenous does not lose their identity because of economic, social, technological conditions. In fact, they are not sufficient enough to discard the peasant customs that have been rooted from generation to generation. It was decided to write a scientific paper in order to encourage academia to address issues related to communication and culture.